Osmotic pretreatment for instant controlled pressure drop dried apple chips: Impact of the type of saccharides and treatment conditions. Issue 7 (19th May 2019) - Xiao, Min; Bi, Jinfeng; Yi, Jianyong; Zhao, Yuanyuan; Peng, Jian; Zhou, Linyan; Chen, Qinqin
Abstract: Instant controlled pressure drop (ICPD) is an emerging drying technique that can produce fruit chips with crispy texture. To improve the qualities of ICPD-dried apple chips, six types of saccharides with different polymerization were used for osmotic pretreatment on apple slices. Firstly, the effects of different saccharides on the osmotic behavior and texture of ICPD-dried apple chips were evaluated. Then, the effects of osmotic conditions of a selected saccharide, i.e. stachyose, on the qualities of ICPD-dried apple chips were studied. The results showed that sucrose, raffinose, and stachyose could significantly enhance the crispness of the ICPD-dried apple chips. In addition, the ICPD-dried apple chips pretreated with stachyose possessed the highest T g (29.74 °C) and superior porous structure compared with pretreatments using the other saccharides. Moreover, limited color change (ΔE) was found in the samples pretreated with stachyose at 40 °C for 30 min, as well as higher retention of polyphenols. In conclusion, it is confirmed that the types of saccharides significantly influence the qualities of the ICPD-dried apple chips, and osmotic pretreatment at 40 °C for 30 min using stachyose was suggested for improving the overall quality of ICPD-dried apple chips.